THE NEED AND SPECIFIC CHARACTERISTICS OF SPIRITUAL PROPAGATION IN GLOBALIZATION - Nuriddin YAKUBJANOV (Scholar Express Journal, 2023)
In this article, the changes taking place in the world during globalization, the necessity and specific features of spiritual propaganda in the conditions of globalization, the reasons for the origin of ideological threats, and the negative consequences caused by such foreign ideas are described on the basis of concrete facts. Also, the article contains suggestions about the methods of promoting spiritual and educational campaigns that should be conducted among the population in the era of globalization
Keywords: globalization; political culture; threat; spirituality